Faktor Sukses Meningkatkan Partisipasi Masyarakat dalam Participatory Budgeting Dengan Metode AHP (Komisi Pemberantasan Korupsi, 2022)
Some countries have enjoyed the adoption of Participatory Budgeting (PB) with real impact. In Brazil, Participatory Budgeting increases local revenues; in New York there is a change in budget allocation based on demand; whilst in the Czech Republic, Participatory Budgeting has succeeded in increasing the number of general election participants. Participatory Budgeting has created opportunities for citizens to be involved, educated and empowered. It helps increase transparency and has the potential to reduce government inefficiency and corruption. However, participatory budgeting in Indonesia encounters problems regarding the low participation rate amongst people with low incomes, making it only a formality. This study was conducted in order to see how Indonesia may take lessons from the experiences of other countries in the world that have implemented Participatory Budgeting. It can be concluded that the level of public participation in the Participatory Budgeting process is a key factor in learning from the implementation of Participatory Budgeting in countries across America, Europe, Asia and Africa. By increasing the role of Non-Government Organizations (NGOs), we may find that community political awareness and involvement in Participatory Budgeting is encouraged.